Profiling of innate and adaptive immune cells during influenza virus infection reveals sex bias in invariant natural killer T (iNKT) cells - Piotr Humeniuk; Aidan Barrett; Hannes Axelsson; Carmen Corciulo; Christina Drevinge; Alicia Del Carpio Pons; Davide Angeletti; Julia M. Scheffler; Ulrika Islander (Immunity, Inflammation and Disease)
Abstract Background Influenza A virus (IAV) infection leads to significant morbidity and mortality. Biological sex influences the immune responses to IAV infection, resulting in higher mortality in women of reproductive age. Previous studies revealed increased activation of T and B cells in female mice after IAV infection, but extensive analysis of sex differences in both innate and adaptive immune cells over time is lacking. Invariant natural killer T (iNKT) cells are fast‐reacting forces and modulators of immune responses that are important to IAV immunity, but it is not known if the presence and function of iNKT cells differ between females and males. The aim of this study was to determine immunological mechanisms that contribute to the increased disease severity in female mice during IAV infection. Methods Female and male mice were infected with mouse‐adapted IAV and monitored for weight loss and survival. Immune cell populations and cytokine expression in bronchoalveolar lavage fluid, lung, and mediastinal lymph node were determined at three time points after infection using flow cytometry and ELISA. Results The results reveal increased severity and mortality in adult female mice compared to age‐matched males. Female mice show larger increases in innate and adaptive immune cell populations and cytokine production in lung compared to mock on Day 6 postinfection. On Day 9 postinfection, female mice express higher numbers of iNKT cells in lung and liver compared to males. Conclusions This comprehensive analysis of immune cells and cytokines over time following IAV infection reveals increased leukocyte expansion and stronger proinflammatory cytokine responses in female mice during disease initiation. Furthermore, this is the first study to report a sex bias in iNKT cell populations after IAV infection. The data suggests that the process of recovery from IAV‐induced airway inflammation is associated with increased expansion of several different iNKT cell subpopulations in female mice.